Remanufactured Fashion - Sinha, Pammi; Muthu, Subramanian Senthilkannan; Dissanayake, Geetha (Environmental Footprints and Eco-design of Products and Processes,, 2016)
This book highlights the concept and applications of Remanufactured Fashion. The first book on this subject, it covers reverse logistics, exemplars, and case studies of remanufactured fashion design. Textile waste is a major issue for all countries, and converting that waste into useful products offers a sensible solution. Remanufactured Fashion is one such sustainable waste management strategy. It involves the conversion of discarded garments into useful retail products, without which they would be dumped at landfills, posing a number of environmental issues. Remanufacturing recovers a product's inherent value once that product no longer fulfills the user's desired needs. The application and use of discarded clothing in remanufacturing processes could greatly reduce the percentage of clothing waste (and mitigate related waste management issues), while also contributing to resource conservation. There has been scant research investigating what is actually involved in the fashion remanufacturing process and how the process could be up-scaled to the mass market in order to achieve greater environmental gains. This book addresses that gap in the literature and examines all aspects pertaining to the concept and applications of Remanufactured Fashion.